INTERAKSI DAN PEMAHAMAN HADIS (TELAAH HERMENEUTIS PEMIKIRAN YUSUF AL-QARADAWI) - Khoiri, M. Alim (UNIVERSUM, 2018)
He also shows how Muslim should do ideal interaction with sunnah. This research is a literature study namely analyzing data related to the topic by checking the references related to the main study especially Yusuf al-Qaradawi’s thought about hadith. In addition, other books are also used as secondary sources of the research. In analyzing the data, this research employs hermeneutic analysis namely describing the discussion object systematically and then analyzing it by using hermeneutic paradigm. In conclusion, the Qaradawi’s theories are not something new and original since they are related to the thoughts developed previously. However, the important contribution of Qaradawi’s theories is placed in the implementation of the theories on the cases related to the contemporary problems. Keywords: al-Qaradawi, hadist, hermeneutica